The role of ADAMTS‐13 in the coagulopathy of sepsis. (2nd February 2018) - Levi, M.; Scully, M.; Singer, M.
Abstract : Summary: The interaction between platelets and the vessel wall is mediated by various receptors and adhesive proteins, of which von Willebrand factor (VWF) is the most prominent. The multimeric size of VWF is an important determinant of a more intense platelet–vessel wall interaction, and is regulated by the VWF‐cleaving protease ADAMTS‐13. A deficiency in ADAMTS‐13 leads to higher concentrations of ultralarge VWF multimers and pathological platelet–vessel wall interactions, in its most typical and extreme form leading to thrombocytopenic thrombotic purpura, a thrombotic microangiopathy characterized by thrombocytopenia, non‐immune hemolysis, and organ dysfunction. Thrombotic microangiopathy associated with low levels of ADAMTS‐13 may be a component of the coagulopathy observed in patients with sepsis. Here, we review the potential role of ADAMTS‐13 deficiency and ultralarge VWF multimers in sepsis, and their relationship with sepsis severity and prognosis. In addition, we discuss the possible benefit of restoring ADAMTS‐13 levels or reducing the effect of ultralarge VWF as an adjunctive treatment in patients with sepsis.